1975
DOI: 10.1139/b75-065
|View full text |Cite
|
Sign up to set email alerts
|

The temperature dependence of thallus nitrogenase activity in Peltigera canina

Abstract: Comparative rates of nitrogen fixation in the lichen Peltigera canina from subarctic and temperate habitats have been examined using the acetylene reduction method. Maximum acetylene reduction at thallus saturation and with 20000 lx illumination takes place at 16 °C in subarctic material and at 21 °C in temperate material. This adaptation of nitrogenase activity to temperature in P. canina is discussed in relation to low levels of soil nitrogen in arctic systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1976
1976
1996
1996

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…If climate warming in the Arctic results in no change in the duration of physiological activity of these common lichens, then a greater increase in nitrogen fixation than photosynthesis is possible. This prediction is consistent with laboratory studies, in which temperature optima at approximately 20°C for ARA has been observed in several species (Kallio & Kallio 1978;Maikawa & Kershaw 1975). At Anaktuvuk Pass, temperatures during maximal acetylene reduction periods rarely exceeded 12°C (Olafsen 1989).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…If climate warming in the Arctic results in no change in the duration of physiological activity of these common lichens, then a greater increase in nitrogen fixation than photosynthesis is possible. This prediction is consistent with laboratory studies, in which temperature optima at approximately 20°C for ARA has been observed in several species (Kallio & Kallio 1978;Maikawa & Kershaw 1975). At Anaktuvuk Pass, temperatures during maximal acetylene reduction periods rarely exceeded 12°C (Olafsen 1989).…”
Section: Discussionsupporting
confidence: 90%
“…Controlled laboratory studies clearly show that both photosynthesis (Kappen 1988) and nitrogen fixation (Maikawa & Kershaw 1975) of polar lichens increase with increasing temperatures up to optimum levels, above which they are observed to decline. Although an interaction of temperature with light may occur such that higher temperature optima occur at higher light levels (Kappen 1988), prevailing temperatures during periods of physiological activity in the field are frequently suboptimal (Carstairs & Oechel 1978) and hence one might a priori predict that global warming will enhance both photosynthesis and nitrogen fixation in Arctic lichens.…”
Section: Introductionmentioning
confidence: 99%
“…Air temperature affects nitrogenase activity in a species-specific manner. The temperature for optimal activity in lichens is between 20 to 30°C (Kershaw 1985), but ranges from 15°C in Solorina crocea and Nephroma arcticum (Kallio et al 1972in Kershaw 1985, to 16-2VC in Peltigera canina (Maikawa and Kershaw 1975), to 35°C in Peltigera rufescens (Hitch and Stewart 1973). However, at high temperatures the lichens and algae tend to rapidly dry out, so a higher level of nitrogen fixation does not mean greater long-term production.…”
Section: United Statesmentioning
confidence: 99%
“…There has been considerable interest in recent years, in the rates of nitrogenase activity in lichens, and particularly in the environmental control of these rates. Thus, moisture content of the thallus (Kershaw, 1974), the length of previous periods of desiccation (Henriksson and Simu, 1971), light intensity (Kallio, Suhonen and Kallio, 1972;Hitch, 1971) and thallus temperature (Hitch, 1971;Kallio, 1973;Maikawa and Kershaw, 1975), have all been shown to affect nitrogenase activity in lichens. The level of activity during dark periods is also of importance and information available on this point is inconsistent.…”
Section: Introductionmentioning
confidence: 99%